THE DEVELOPMENT AND EXPRESSION FORM OF MANCHU SHAMAN MUSIC - Cui Yumeng; Nadia Madzhi (Journal of Islamic, Social, Economics and Development, 2023)
Manchu is an ancient nation, with its own language and rich culture. Their ancestors believed in Shamanism and worshipped nature, totem and ancestors. The host of Shamanism was called Shaman. Although Shamanism did not have a unified religious code, a complete and strict religious organization, and no fixed places for activities, Shaman sacrificial activities still continued to this day. In Shaman activities, Shaman music is a very characteristic form, with rich drum music and lyrics. Its origin and development are closely related to Manchu history and culture, religious customs and the life of human society. The purpose of this paper is to introduce the origin and development of Shamanic music and the characteristics of Shamanic music culture, analyze Shamanic music through three forms of expression: Shaman god song, Shaman instrument and Shaman dance, and explore the significance of shamanic music research to traditional national culture.